Flagship 4: Social protection for agriculture and resilience - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2018)
Cash, food, or vouchers—which and when? ● Programs that deliver more security and better nutrition at lower cost ● Linking social protection and agricultural development ● What does it mean to graduate? ● What works in fragile and conflict-affected setting?